2008
DOI: 10.1007/s11357-008-9055-2
|View full text |Cite
|
Sign up to set email alerts
|

Explaining longevity of different animals: is membrane fatty acid composition the missing link?

Abstract: Saturated and monounsaturated fatty acids are very resistant to peroxidative damage, while the more polyunsaturated a fatty acid, the more susceptible it is to peroxidation. Furthermore, the products of lipid peroxidation can oxidatively damage other important molecules. Membrane fatty acid composition is correlated with the maximum lifespans of mammals and birds. Exceptionally long-living mammal species and birds have a more peroxidation-resistant membrane composition compared to shorter-living similar-sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 39 publications
(42 reference statements)
3
39
0
Order By: Relevance
“…Our finding of phospholipid metabolic process proteins corroborates previous results suggesting a role of lipid metabolism in species differences in longevity (Hulbert 2008;Jobson et al 2010). It has been reported that membrane fatty acid composition is correlated with the maximal lifespans of mammals through the reduction of oxidative damage caused by products of lipooxidation (Hulbert 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of phospholipid metabolic process proteins corroborates previous results suggesting a role of lipid metabolism in species differences in longevity (Hulbert 2008;Jobson et al 2010). It has been reported that membrane fatty acid composition is correlated with the maximal lifespans of mammals through the reduction of oxidative damage caused by products of lipooxidation (Hulbert 2008).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that membrane fatty acid composition is correlated with the maximal lifespans of mammals through the reduction of oxidative damage caused by products of lipooxidation (Hulbert 2008). Proteins belonging to the lipid biosynthetic process were also identified in our analysis which have previously been linked to the peroxidative damage via increased saturation and to the control of mitochondrial ROS production by reducing membrane potential and increasing the efficiency of ETC uncoupling (Kua 2006;Jobson et al 2010).…”
Section: Discussionmentioning
confidence: 72%
“…Both paraquat and H 2 O 2 are well-known oxidative stressors, and there is evidence that the lethal effects of both Cd (Brennan and Schiestl, 1996;FigueiredoPereira et al, 1998;Shukla et al, 2000) and MMS (Mizumoto et al, 1993;Wilhelm et al, 1997) are at least partially mediated by oxidative stress; indeed, differences in the susceptibility of cell membranes to peroxidation are strongly associated with species lifespan Hulbert et al, 2006;Hulbert et al, 2007;Mitchell et al, 2007;Buttemer et al, 2008;Hulbert, 2008;Hulbert et al, 2008). Nevertheless, the mechanism(s) by which cells can augment resistance to multiple forms of lethal stress and metabolic perturbation are still unknown and are under active investigation (Lithgow and Miller, 2008;Williams et al, 2010), with the evaluation of co-evolutionary patterns likely to contribute to this developing story.…”
Section: Discussionmentioning
confidence: 99%
“…The "membrane pacemaker hypothesis of ageing" predicts that long-living species will have more peroxidation-resistant membrane lipids than shorter-lived species [27] . Polyunsaturated fatty acids, particularly those from the n-3 class, are highly susceptible to peroxidation and are key suspects for the propagation of cellular oxidative stress [27] .…”
Section: Tissue Fatty Acid Composition and Ageingmentioning
confidence: 99%